An alternative method for sourceless density measurement with boron sleeve gamma detectors. (August 2021) - Zhang, Quanying; Deng, Rui; Zhang, Shengqiang; Zhang, Feng; Liu, Jiayi; Liao, Huimei
Abstract: Neutron gamma density measurement using dual gamma detectors (NGD-GD) is a popular density measurement method. Compared with other NGD methods, the NGD-GD method has many advantages in tool optimization, cost control, and density precision; however, it is easily affected by the salinity of formation water. To improve the NGD-GD method, the influence mechanism of formation water salinity was discussed, and a feasible improvement scheme using characteristic gamma information was proposed. A special boron sleeve gamma detector was designed to record the capture gamma rays from the boron-10 element. By analyzing the gamma spectrum, pure boron-10 gamma information was extracted from the total capture gamma spectrum for density calculation. Finally, a new NGD method with boron sleeve gamma detectors (NGD-BD) was developed. Results depict that although the NGD-BD method has a slight decrease in density accuracy and precision compared with the NGD-GD method, its performance is significantly improved in high-brine formations, and oil and gas formations. In addition, the NGD-BD method exhibits better performance in terms of density accuracy, density precision, and environmental impact than another NGD method that uses hydrogen capture gamma information. Moreover, the NGD-BD method is easily implemented with low cost and has little impact on existing NGD tools, and hence, it can coexist with other NGD methods to improve logging quality. Overall, the NGD-BD method is a very promising alternative to the NGD-GD method.